Gradient mineralized collagenous fiber membrane as well as preparation method and application thereof
Through gradient mineralization, high-oriented collagen fiber membranes simulate the tendon-bone interface structure, the shortcomings of existing tendon substitutes in biological activity and mechanical properties are solved, effective regeneration and healing of tendon-bone interface are achieved, and tendon-bone interface is enhanced. Biocompatibility and mechanical properties of bone interfaces.
Patent Information
- Application Number
- CN202411127959.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2024-12-13
AI Technical Summary
Existing tendon alternatives have shortcomings in bioactivity, mechanical properties and biocompatibility, which are difficult to effectively promote the regeneration and healing of the tendon-bone interface, and traditional treatments are also difficult to reconstruct the complex transition structure of the attachment point.
Using gradient mineralized high-oriented collagen fiber membranes, simulate the structural and mechanical properties of the tendon-bone interface by forming gradient mineralized and unmineralized layers in the membrane, providing a more bionic environment to promote cell attachment and differentiation. .
It significantly improves the healing effect of the tendon-bone interface, enhances mechanical properties and biocompatibility, promotes the regeneration of tendons and bones, and improves the recovery of animal motor function.
Smart Images

Figure CN119113215A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of tissue repair in biomedical materials, relates to a gradient mineralized collagen fiber membrane, and also includes a preparation method and application thereof. Background Art
[0002] The attachment point is the tissue connecting tendons and bones. Its complex gradient morphology, chemical composition and physicochemical properties are crucial to the execution of tendon-bone physiological functions. In recent years, with the vigorous promotion of national fitness, the incidence of tendon-bone injuries has been on the rise. The natural tendon-bone interface is composed of transitional tissue composed of layered fibrocartilage, which ensures a firm connection between tendons and bones and effectively transmits stress; according to the degree of proximity to the bone surface from low to high, the tendon-bone interface is divided into tendon fiber zone, unmineralized fibrocartilage zone, mineralized fibrocartilage zone and bone zone. Tendon injuries are very common in clinical practice, and reconstruction of the tendon-bone interface is a key link in the treatment process. However, problems such as long rehabilitation period, strain-dependent scar formation and poor vascularization have led to huge challenges in restoring natural tendon-bone (attachment point tissue) after surgery.
[0003] Biologically based strategies to promote tendon-bone interface regeneration mainly include the application of bioactive materials, appropriate seed cells or stem cells, growth factors and gene delivery to the reconstructed interface. However, to date, few of these alternatives have provided successful long-term solutions. Traditional tendon implant materials, such as ligament augmentation and reconstruction systems based on polyethylene terephthalate (PET), have been widely used in the field of tendon implantation. and Gore-Tex, although they have excellent mechanical properties, they lack biological activity and cannot promote appropriate new tissue growth and effective integration with host tissue, resulting in poor tendon-bone interface healing and even complications. In addition, although allografts and autografts retain the structure and composition of natural tendons, as well as bioactive molecules, negative effects such as donor site morbidity, adverse immune responses, and synovitis limit their clinical application.
[0004] Current tendon replacements have the following common problems:
[0005] A. Most tendon substitutes do not have good bioactivity: artificial ligaments made of non-degradable polymers, such as polyethylene terephthalate (PET)-based ligament augmentation and reconstruction systems Although they have excellent mechanical properties, they lack satisfactory bioactivity and cannot achieve new tissue ingrowth and good integration with host tissue, resulting in poor healing of the tendon-bone interface and even complications such as synovitis and long-term implant failure.
[0006] B. Limitations of developing similar heterogeneous transition regions: Single-phase scaffolds have uniform structure and composition, and it is usually impossible to completely reconstruct soft tissue and hard tissue and their interfaces. Biphasic scaffolds have a two-phase layered structure, and the composition, internal structure and mechanical properties of each layer are usually different. They can meet the requirements of cartilage and subchondral bone implantation and repair at the same time, but the biphasic scaffold has poor integration at the damaged tendon-bone interface and weak mechanical stability, which is not conducive to defect repair. In the multiphase scaffold design, the scaffold is isolated into three or more layers, and the layers show abrupt transition properties, and it is still challenging to reconstruct functional natural attachment points.
[0007] C. Traditional conservative treatment or surgical repair mainly focuses on reconstructing the anatomical structure of the attachment point, while ignoring the regeneration of the attachment point tissue: Traditional surgical treatment mainly uses the ruptured tendon end to reconstruct the attachment point: first, the ruptured tendon is directly inserted into the bone tunnel, and then the reconstructed tissue is mechanically anchored using sutures or screws, and external loads are minimized to avoid accidental loosening or re-tearing after surgery. However, the reconstructed attachment point may maintain a weak connection with the bone for a long time, resulting in the formation of scar tissue at the rupture instead of the required healthy attachment point tissue, which lacks the reconstruction of the complex transition between tendon and bone. Therefore, traditional conservative treatment or surgical repair has limited efficacy in tendon-bone injury repair.
[0008] Therefore, there is an urgent need for a new type of tendon substitute with excellent biocompatibility, bioactivity and mechanical properties that can promote the regeneration of the natural tendon-bone interface. Biomaterials that mimic the natural tendon-bone interface can provide a favorable environment for the regeneration of damaged interface tissue and induce in situ regeneration of attachment tissue at the site of injury. Collagen is the main component of the extracellular matrix (ECM) of human tendons and has excellent biocompatibility and bioactivity. Well-arranged collagen fiber materials that mimic the physiological ECM of tendons are considered to be ideal materials for tendon tissue engineering. In order to ensure that the tendon-bone interface scaffold is highly biomimetic, the internal structure of the attachment scaffold needs to be carefully designed. Considering the gradient characteristics of the structure, mechanical properties, chemical properties and cell phenotype of the tendon-bone interface, designing biomimetic materials with structural, mechanical and biochemical gradients can help promote the regeneration of the tendon-bone interface. Summary of the invention
[0009] The technical problem to be solved by the present invention is to provide a tendon repair material with a gradient mineralized layer to better simulate the natural tendon-bone connection structure and promote tendon-bone interface healing.
[0010] The invention provides a gradient mineralized (highly oriented) collagen fiber membrane, comprising a gradient mineralized layer and a non-mineralized layer.
[0011] The gradient mineralization layer includes type I collagen component and HAp (hydroxyapatite) component with spatial gradient distribution,
[0012] The unmineralized layer is composed of type I collagen components.
[0013] Preferably, the type I collagen component has a highly oriented fiber structure, and the Herman orientation factor of the fiber structure is distributed in the range of 0.92-0.99.
[0014] Generally speaking, due to mineralization, the thickness and width of the gradient mineralized layer are slightly greater than the thickness and width of the unmineralized layer, but the difference in thickness and width can be ignored. Preferably, the width of the gradient mineralized layer can be 1-1.5 times the width of the unmineralized layer, and the thickness of the gradient mineralized layer can be 1-1.5 times the thickness of the unmineralized layer. Preferably, the width of the gradient mineralized layer is the same as the thickness.
[0015] Preferably, the length ratio of the gradient mineralized layer to the unmineralized layer is (1-9):(1-9), more preferably (7-8):(2-3).
[0016] On the other hand, the present invention provides a method for preparing the above-mentioned gradient mineralized collagen fiber membrane. The collagen fiber membrane is placed vertically at the bottom of a container along the fiber orientation direction, and then a mineral solution is continuously injected into the container at a rate of 0.3-0.7 ml / h, and mineralized at a constant temperature of 35°C-39°C. After the mineralization is completed, the excess mineralized liquid on the surface is removed, and then it is dried at a constant temperature of 35°C-39°C.
[0017] Preferably, after the highly oriented collagen fiber membrane is placed vertically at the bottom of the container, the mineral solution is continuously injected into the container at a rate of 0.5-0.6 ml / h. Then, constant temperature mineralization and / or drying is performed, and the temperature is preferably 36°C-38°C), and more preferably, the temperature is set to 37°C.
[0018] Preferably, the pH value of the mineral solution is 7.37-7.49, and it comprises a uniformly mixed solution A component and a solution B component of equal volume. The pH value of the mineral solution is preferably 7.40-7.42.
[0019] Wherein, solution A component is a mixed solution of 0.1M CaCl2·2H2O and 0.02-0.04g / ml polyaspartic acid solid powder; preferably, the content of polyaspartic acid solid powder in solution A component is 0.03-0.04g / ml; more preferably, the content of polyaspartic acid solid powder in solution A component is 0.03g / ml. Solution B component is selected from at least one of a mixed solution of 0.1M Na2HPO4 and 0.04-0.08g / ml polyacrylic acid solid powder or a mixed solution of 0.1M K2HPO4 and 0.04-0.08g / ml polyacrylic acid solid powder. Preferably, the content of polyacrylic acid solid powder in solution B component is 0.06-0.08g / ml; more preferably, the content of polyacrylic acid solid powder in solution B component is 0.06g / ml. The content of the polyaspartic acid solid powder in the solution A component: the content of the polyacrylic acid solid powder in the solution B component is 1: (1.5-2.5), preferably, 1:2.
[0020] Preferably, the molecular weight of the polyaspartic acid solid powder is 10-11 kDa, and the molecular weight of the polyacrylic acid solid powder is not less than 2000 Da; the mass concentration ratio of the polyaspartic acid solid powder to the polyacrylic acid solid powder is 1:2.
[0021] Preferably, the mineral solution is selected from any one of the following formulas:
[0022] Ⅰ: 9mM CaCl2·2H2O+4.2mM K2HPO4+50μg / mL pAsp;
[0023] Ⅱ: 10.0mM CaCl2·2H2O+6.0mM Na2HPO4+90mM NaCl+350μg / ml PAA+10mM L-Glutamic acid;
[0024] III: 1.67mM CaCl2·2H2O+9.5mM Na2HPO4+150mM NaCl+240μg / mL pAsp+Sodiumcitrate;
[0025] IV: SBF + 180 μg / mL pAA + 2.5 wt% TPP; or
[0026] V: Solution A: 0.1M CaCl2·2H2O+0.03g / mL pAsp; Solution B: 0.1M Na2HPO4+0.06g / mL PAA.
[0027] The experimental results of the present invention show that the mineral contents of the five formulas increase in sequence, and the HAp characteristic crystal diffraction peaks of formulas II, IV and V are significantly higher than those of the other two groups, and formula V shows the strongest HAp characteristic crystal diffraction peak.
[0028] In the present invention, the method for preparing the highly oriented collagen fiber membrane comprises the following steps:
[0029] The collagen gel membrane stretched to 100%-200% strain is immersed in a 0.1M PBS solution for 1-4 hours (preferably 2-3 hours), while continuously loading both ends of the membrane to maintain the oriented structure;
[0030] After soaking, the collagen gel membrane is placed in an NH3 atmosphere for 12-36 hours (preferably 24-30 hours), and external force is continuously applied to both ends of the collagen gel membrane.
[0031] In another aspect, the present invention provides the application of the gradient mineralized high-oriented collagen fiber membrane, and the application of the gradient mineralized high-oriented collagen fiber membrane in tendon-bone repair.
[0032] Preferably, the application includes one or more of the following:
[0033] (1) It has an aligned hierarchical fibrous structure and enhances mechanical properties in the alignment direction:
[0034] (2) Supporting the adhesion and continued proliferation of cells associated with tendon and bone healing;
[0035] (3) allowing the provision of different local physicochemical environments to selectively promote cell differentiation into tendon, cartilage, or bone, thus potentially reconstructing the gradient cell phenotype of tendon-bone interface tissue;
[0036] (4) Enhance the mechanical properties of the healing injury site and the recovery of the animal's motor function.
[0037] In the present invention, AHF-Col refers to a highly oriented collagen fiber membrane obtained after stretching. Figure 1 The following figure (such as Figure 8 ) refers to the highly oriented collagen fiber membrane obtained by stretching the electrochemically assembled collagen gel membrane E-Col to 200% strain and then soaking in physiological ion solution and incubating in NH3 atmosphere for 24 hours.
[0038] like Figure 1 As shown, Figure 1AHF-Cols refers to the electrochemically assembled collagen gel membrane E-Col, which is stretched to different strains (50%, 100%, 150%, 200%) and then soaked in physiological ion solution and incubated in NH3 atmosphere for 24 hours to obtain collagen fiber membranes with different degrees of orientation structure. RF-Col refers to the electrochemically assembled collagen gel membrane E-Col, which is not stretched, but soaked in physiological ion solution and incubated in NH3 atmosphere for 24 hours to obtain a collagen fiber membrane with approximately non-oriented structure. Figure 1 The following figure (such as Figure 8 ) specifically refers to the electrochemically assembled collagen gel membrane E-Col, which is stretched to 200% strain and then soaked in physiological ion solution and incubated in NH3 atmosphere for 24 hours to obtain a highly oriented structural collagen fiber membrane.
[0039] GMA-Col refers to a highly oriented / gradient mineralized collagen fiber membrane obtained after gradient mineralization, and refers to a highly oriented / gradient mineralized collagen fiber membrane obtained after gradient mineralization of AHF-Col (a highly oriented structural collagen fiber membrane with 200% strain) using mineralization scheme V.
[0040] MAHF-Col is a mineralized / highly oriented collagen fiber membrane. MAHF-Cols is a highly oriented / mineralized collagen fiber membrane obtained by mineralizing the above-mentioned 200% strained highly oriented structural collagen fiber membrane AHF-Col (the mineralization method here is not gradient mineralization, but mineralization of the entire AHF-Col (200% strain) material); s is added because the mineralization effects of five mineralization schemes (Ⅰ-Ⅴ) on AHF-Col were explored and compared ( Figure 8 cd, Fig. 9 ) The best mineralization scheme V was selected, and then the relevant physical and chemical properties of the highly oriented / mineralized collagen fiber membrane MAHF-Col (V) obtained after AHF-Col (200% strain) mineralized using mineralization scheme V were investigated ( Figure 8 en).
[0041] The beneficial effects of the present invention are as follows:
[0042] (1) AHF-Col has an aligned hierarchical fibrous structure and exhibits enhanced mechanical properties in the aligned direction: The mechanical properties of AHF-Col significantly increase with the degree of orientation, and AHF-Col prepared under 200% strain conditions has the highest tensile strength (95.97±1.6MPa) and Young's modulus (5.06±0.07Gpa) in the dry state. (The strength of native tendon tissue from different animals varies between 55 and 120MPa).
[0043] (2) Gradient mineral content facilitates spatially continuous variation of mechanical stiffness: Gradient mineral content is essential for the natural integration of tendon to bone and provides a mechanism for spatially continuous variation of mechanical stiffness, thereby eliminating high stress at the interface and effectively transferring mechanical loads from tendon to bone. Constructing a mineral content gradient in the implant can not only better adapt to the transition of mechanical stiffness from tendon to bone in vivo, but also has the potential to provide heterogeneous physicochemical cues (e.g., stiffness, composition) for spatial cell phenotypes, promoting tendon-to-bone reconstruction. Controlling the spatial and temporal penetration of mineralizing solutions into the scaffold provides a potential method for generating mineral gradients on AHF-Col. The gradient distribution of HAp within and between fibers in the material can mimic the hierarchical spatial distribution of minerals in bone, ensuring a smooth transition of mechanical properties from relatively flexible soft tissue to rigid hard tissue.
[0044] (3) Differentiation of local areas on GMA-Col Surface morphology, mineral content, stiffness, and wettability affect cell adhesion, proliferation, and differentiation to a certain extent: Different areas of GMA-Col showed good biocompatibility, supporting the adhesion and sustained proliferation of cells associated with tendon and bone healing. In addition, these results may indicate that GMA-Col allows the provision of different local physicochemical environments that can spatially selectively promote cell differentiation into tendon, cartilage, or bone, thereby potentially reconstructing the gradient cell phenotype of tendon-bone interface tissue.
[0045] (4) Implantation of GMA-Col significantly enhanced the mechanical properties of the healed injury site and the recovery of the animal's motor function: the newly formed tendon tissue showed mature collagen expression and organizational arrangement, while the reconstructed attachment point tissue formed mature fibrocartilage, showing permeability and tight connection with the regenerated bone tissue. More encouragingly, the implantation of this material significantly enhanced the mechanical properties of the healed injury site and the recovery of the animal's motor function. Overall, this bionic implant / patch material has excellent mechanical properties and gradient biological functions, showing great potential for comprehensive regeneration from tendon to bone. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the technical solution of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, each drawing in the following description is for some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0047] Figure 1Preparation, structural and mechanical characterization of aligned hierarchical fibrillar collagen structures. (b) Polarized optical microscopy images of AHF-Cols under different strains show that the optical birefringence gradually increases in a strain-dependent manner, indicating that the alignment of AHF-Cols is strain-induced. (c) Low-magnification SEM images and (d) high-magnification SEM images and (e) two-dimensional SAXS images of AHF-Cols under different strains (fc is the Herman orientation parameter) show that AHF-Col with a strain rate of 200% has the best aligned hierarchical fiber structure. (f) One-dimensional SAXS patterns confirm the formation of D bands in AHF-Cols. (g) Stress-strain curves of dried AHF-Cols along the orientation and (h) quantitative ultimate stress and Young's modulus of dried samples show that AHF-Col with a strain rate of 200% has the highest mechanical properties. Statistical analysis was performed using one-way ANOVA with Tukey's post hoc test: *P<0.05, **P<0.01, ***P<0.001. P is the statistical probability. The smaller the p value, the smaller the probability, indicating that the difference is more significant. The same below.
[0048] Figure 2 Gradient mineralization structure and resulting gradient properties of GMA-Col. (a) Schematic diagram showing that GMA-Col with gradient mineral composition can be constructed by controlling the spatial and temporal penetration of the mineralizing solution into AHF-Col. (b) GMA-Col stained with Alizarin Red S shows a red gradient along the long axis (i.e., alignment direction), indicating that the mineral content deposited in GMA-Col varies in a gradient along the alignment direction. (c) Low-magnification and (d) high-magnification SEM images and (e) EDS elemental images of different regions on GMA-Col show that gradient sedimentary minerals exist on the surface of the mineralized area of GMA-Col, while the surface of the non-mineralized area shows an inherent aligned fibrous structure. (f) TEM images of different regions on GMA-Col show different degrees of internal mineralization. (g) The corresponding AFM property images show that the surface modulus of different regions on GMA-Col increases with the increase of mineralization degree. (h) Quantitative calcium content, (i) local surface modulus, and (j) water contact angle changes along the mineralization gradient, with the x-axis representing the distance to the location with the highest mineral content [i.e., the bottom location shown in (a)].
[0049] Figure 3Different regions of GMA-Col promote spatially dependent promotion of cells toward tenogenic, chondrogenic, and osteogenic phenotypes. Immunofluorescence staining images of TSPCs cultured on (a) RF-Col and (b) GMA-AF for 24 h, and representative distributions of cytoskeletal shape (ratio of line length to eccentricity) and orientation (line angle). Statistical analysis of quantification (c) aspect ratio and (d) area of TSPCs. (e) mRNA transcript levels of teno-lineage genes in TSPCs cultured on RF-Col and GMA-AF for 14 days. Expression levels were normalized to the housekeeping gene GAPDH. (f) Live / dead staining and (g) quantitative lactate dehydrogenase (LDH) levels of BMSCs after 7 days of culture on different sample surfaces. (m) mRNA transcript levels of chondrogenic and (n) osteogenic genes in BMSCs cultured on different sample surfaces for 14 days. Expression levels were normalized to the housekeeping gene GAPDH. Statistical analysis was performed using one-way ANOVA with Tukey's post hoc test: *P < 0.05, **P < 0.01, ***P < 0.001.
[0050] Figure 4 Implantation of GMA-Col can promote structural renewal of injured tendons in the rabbit RCT model. (a) (i-iii) Gross morphology of rotator cuff tissue exposure, defect formation, and patch implantation. (iv) Schematic diagram of rotator cuff patch application. Representative (b) hematoxylin and eosin (H&E) staining of newly formed tendon tissue around implants at 4 and 8 weeks after surgery, and immunohistochemical staining images of (c) Col I and (d) Col III expression in newly formed tendon tissue around implants at 4 and 8 weeks after surgery in different groups. (n = 4 rabbits per group). (e) Immunofluorescence staining images of glycoprotein Tenascin-C (TNC) expression at 4 and 8 weeks after surgery. Semi-quantification of the area ratio of (f) Col I and (g) Col III expression in newly formed tendon tissue based on the immunohistochemical staining images in (c) and (d), respectively, and (h) the results of TNC staining cells based on the immunofluorescence image in (e). (i) Quantitative histological scoring of tendon tissue structure, arrangement, and maturation (see Table S3 for grading criteria). Statistical analysis was performed using one-way ANOVA with Tukey's post hoc test: *P < 0.05, **P < 0.01, ***P < 0.001.
[0051] Figure 5In the rabbit RCT model, implantation of GMA-Col promoted the regeneration of the injured tendon-bone interface from fibrocartilage to bone. Representative images of (a) hematoxylin and eosin (H&E), (b) safranin-fast green (SO-FG), and (c) immunofluorescence staining of cartilage- and bone-forming related markers (Aggrecan / BMP-2) at the tendon-to-bone interface at 8 and 12 weeks after surgery. (n = 4 rabbits per group). (d) Semiquantification of the area of newly formed fibrocartilage according to the results of SO-FG staining. (e) Results of Aggrecan and (f) BMP-2 stained cells and (g) histological scoring of the structural integrity and maturity of the interface tissue (grading criteria are shown in Table S4). (n = 4 rabbits per group). Statistical analysis was performed using one-way ANOVA with Tukey post hoc test: *P < 0.05, **P < 0.01, ***P < 0.001.
[0052] Figure 6 Implantation of GMA-Col promoted microarchitectural reconstruction and bone regeneration at the injured tendon-bone interface in the rabbit RCT model. (a) High-resolution micro-CT images of the tendon-bone interface in different groups showed the integrated transition from tendon to bone at 12 weeks. (b) Comparison of high-magnification micro-CT images of AHF-Col and GMA-Col showed differences in the organization of their tendon-bone intercalation tissues at 12 weeks. (c) Representative micro-CT analysis images of the bones at the tendon-bone interface at 8 and 12 weeks after surgery. Quantification of bone defects at the tendon-bone interface in different groups at 8 and 12 weeks after surgery (d) Bone volume fraction (BV / TV), (e) bone mineral density (BMD), and (f) trabecular number (Tb.N) values at the tendon-bone interface. (n = 4 rabbits per group). Statistical analysis was performed using one-way ANOVA with Tukey post hoc test: *P < 0.05, **P < 0.01, ***P < 0.001.
[0053] Figure 7Implantation of GMA-Col promotes recovery of motor function and enhances tendon-bone interface tissue integration in rabbits with rotator cuff injuries. (a) Representative images of rabbits from different groups running on a treadmill 12 weeks after surgery. (b) Comparison of the movement trajectories of the left forelimb of rabbits from different groups during continuous movement, with adjacent trajectories shown as one frame interval. (c) Schematic diagram of the left forelimb of a rabbit and key joints associated with movement. The rotator cuff joints are marked with red dots, corresponding to different points in the movement trajectory shown in (b). Quantitative analysis based on the continuous movement trajectory of the animals on the treadmill produced (d) jumping speed and (e) maximum jumping height, indicating that rabbits implanted with GMA-Col had enhanced recovery of motor function 12 weeks after surgery. Quantitative analysis of the changes in the movement angle of the rotator cuff relative to the (f) neck and (g) elbow during movement showed that rabbits implanted with GMA-Col had enhanced recovery of shoulder joint mobility 12 weeks after surgery. (h) Representative biomechanical test images of rabbit rotator cuffs 12 weeks after surgery. (i) Ultimate failure load, (j) ultimate tensile strength, and (k) rotator cuff stiffness of each treatment group 12 weeks after surgery. (n = 4 rabbits per group). Statistical analysis was performed using one-way ANOVA with Tukey post hoc test: *P < 0.05, **P < 0.01, ***P < 0.001.
[0054] Figure 8 Characterization of the structure and properties of AHF-Col. (c) Thermogravimetric analysis (TGA) and (d) X-ray diffraction (XRD) results of mineralization of AHF-Cols show that the samples prepared using mineralization protocol V have the highest mineral content and HAp formation. (e) Polarized light microscopy image, (f) SEM micrograph, and (g) TEM micrograph of MAHF-Col obtained using mineralization protocol V, indicating the retention of long-range oriented microstructure and inter- and intrafiber mineral formation. Comparison of (hi) chemical and physical structure, (j) wettability, and (k) surface modulus between AHF-Col and MAHF-Col. (l) Representative stress-strain curves of AHF-Col and MAHF-Col along orientation. Quantitative results of (m) tensile strength and elongation at break, and (n) Young's modulus and toughness show that MAHF-Col has higher mechanical strength compared to AHF-Col. Statistical analysis was performed using one-way ANOVA with Tukey's post hoc test: **P < 0.01, ***P < 0.001.
[0055] Fig. 9 Mineral content and mineral crystallinity of different AHF-Col biomimetic mineralization schemes. (a) Mineral / collagen ratio and (b) mineral crystallinity of different AHF-Col biomimetic mineralization schemes show that the samples obtained with mineralization scheme V have the highest mineral content and the highest mineral crystallinity. DETAILED DESCRIPTION
[0056] The materials and methods involved in the present invention are as follows:
[0057] 1. Preparation and mechanical properties evaluation of highly oriented collagen fiber membrane AHF-Col
[0058] Preparation of electrolyte: Dissolve type I collagen extracted from pig skin in ultrapure water, add glacial acetic acid to adjust the pH to 3.5, and add hydrogen peroxide at a volume ratio of 10:1 to obtain collagen electrolyte.
[0059] Electrochemical assembly of collagen gel membrane: A three-electrode system of electrodeposition is used, with titanium sheet as the working electrode, platinum wire as the counter electrode, and Ag / AgCl as the reference electrode. The three-electrode system is inserted into the configured electrolyte, and the electrode reaction is used to establish a pH gradient to cause the collagen to undergo a phase transition, from a collagen solution to a collagen gel membrane E-Col. Anode: 2H2O–4e - →4H + +O2; cathode: 2H2O+4e - →4OH - +2H2.
[0060] Mechanical stretching induces the formation of oriented structure of collagen gel film: Under the action of a mechanical stretching machine, the electrochemically assembled collagen gel film E-Col is stretched to different strains along the length direction: 0%, 50%, 100%, 150%, 200%, so that the structure of the collagen gel film is further oriented.
[0061] Preparation of highly oriented collagen fiber membrane AHF-Cols: The above collagen gel membranes with different degrees of orientation were immersed in 0.1M PBS physiological ionic environment solution for 2 hours, while continuously loading the two ends of the membrane to maintain the oriented structure. After immersion, the film was placed in NH3 atmosphere for 24 hours, and external force was continuously applied at both ends to induce the growth of oriented collagen microfibrils and the formation of D bands, and then dried. The dried collagen membrane was cross-linked in glutaraldehyde solution (1% w / v in 90% v / v ethanol-water solution) for 30 minutes, and then repeatedly washed with ultrapure water to remove any residual glutaraldehyde. Finally, AHF-Cols prepared under different tensile strain conditions were obtained, and their structure and mechanical properties were further characterized.
[0062] Micromorphological characterization of highly oriented collagen fiber membrane AHF-Cols: Polarized light microscopy (POM, AxioScope A1) and scanning electron microscopy (SEM, S4800 Hitachi) were used to observe the orientation structure and surface morphology of collagen fiber membrane AHF-Cols with different strain degrees, and small-angle X-ray scattering (SAXS) was used to observe the internal structure of AHF-Cols and its microstructure (i.e., D-band formation, Herman orientation factor).
[0063] Mechanical property evaluation of highly oriented structural collagen fiber membrane AHF-Cols: Collagen gel membrane AHF-Cols with different strain degrees was cut into rectangles, tensile tests were carried out at room temperature, and the thickness was measured by an electronic thickness gauge. The static tensile properties of the samples at room temperature were measured using a dynamic biomechanical testing system (Electro-3220, USA). For static mechanical testing, the tensile rate was set to 0.05 mm / s (0.17% / s). The strain of the sample was calculated by dividing the length change at break by the initial distance between the clamps. The stress was calculated as the force applied to the sample divided by the initial cross-sectional area. The tensile breaking strength and elongation at break of the collagen fiber material samples at different tensile strains were determined by stress-strain curves. Young's modulus was calculated based on the slope of the initial linear region of the stress-strain curve.
[0064] 2. Preparation and evaluation of physicochemical properties of gradient mineralized highly oriented collagen fiber membrane GMA-Col
[0065] Preparation of gradient mineralized highly oriented collagen fiber membrane GMA-Col: According to the mineralization solution formula [Solution A: CaCl2·2H2O (0.1M) + pAsp (polyaspartic acid, molecular weight about 10000, 0.03g / ml), solution B: Na2HPO4 (0.1M) + PAA (polyacrylic acid, molecular weight about 2000, 0.06g / ml); equal volumes of solution A and solution B were mixed evenly and the pH value was adjusted to 7.4 using NaOH solution], the mineralization solution was prepared. The prepared 200% strain highly oriented collagen fiber membrane AHF-Col was placed vertically at the bottom of the beaker, and then the prepared mineral solution was filled into a 10mL plastic syringe, and the solution was continuously injected into the beaker at a speed of 0.5ml / h using a syringe pump, and mineralized at a constant temperature of 37℃ for 7 days. During the entire mineralization process, the mineralization solution in the syringe pump was replaced every 12 hours to ensure the mineralization effect. As the mineral solution is gradually added to the beaker, the minerals are gradually deposited on the highly oriented collagen fiber membrane AHF-Col immersed in the solution. As the level of the mineral solution in the beaker rises, a gradient of mineral content is formed due to the different immersion times at the upper and lower ends of the highly oriented collagen fiber membrane AHF-Col. After the mineralization is completed, the material is rinsed with ultrapure water to remove excess mineralization liquid on the surface, and then placed in a 37°C electric constant temperature blast furnace overnight for drying. The resulting highly oriented / gradient mineralized collagen fiber membrane is named GMA-Col.
[0066] Gradient structure characterization of GMA-Col: The prepared highly oriented / gradient mineralized collagen fiber membrane GMA-Col was immersed in Alizarin Red solution (40mM) for 3 hours, and then the surface of the material was thoroughly washed with ultrapure water to remove the residual dye. After air drying, macroscopic photos of GMA-Col were taken using a digital camera. Scanning electron microscopy (SEM, Helios G4 UC) was used to examine the morphology of mineral crystals deposited at different positions along the long axis of GMA-Col. At the same time, X-ray energy dispersive spectroscopy (EDS) was used to determine the elemental composition and distribution at different positions along the long axis of GMA-Col, and the Ca / (Ca+C) atomic ratio was obtained. Transmission electron microscopy (TEM, JEM-2100) was used to observe the spatial morphology of collagen fibers and deposited mineral crystals in GMA-Col. Atomic force microscopy (AFM, MFP-3D) was used to perform high-resolution scanning of the GMA-Col surface to obtain the morphological characteristics of the sample surface, and the surface modulus at four positions along the mineral gradient of GMA-Col was measured.
[0067] Evaluation of the hydrophilic and hydrophobic properties of GMA-Col: A contact angle meter (JC2000D3) was used to characterize the hydrophilic and hydrophobic properties of GMA-Col. GMA-Col was placed on a test bench, 10 μL of ultrapure water was dripped on different positions on the material surface, and the contact angle between the material surface and the water droplet was measured.
[0068] 3. Evaluation of the biological properties of gradient mineralized highly oriented collagen fiber membrane GMA-Col
[0069] Cytocompatibility of GMA-Col:
[0070] To investigate the cytocompatibility of GMA-Col, the samples were segmented along their longitudinal axis according to the gradient distribution of mineral content (Ca / Ca+). The mineral deposition of GMA-Col from high to low was zone I (GMA-HM with rich mineral deposition), zone II-a (GMA-MM with moderate mineral deposition), zone II-b (GMA-LM with minimal mineral deposition), and zone III (GMA-AF with no mineral deposition). Circular samples with a diameter of 10 mm were cut from each zone and placed in 48-well plates for cell culture studies. GMA-HM, GMA-LM, GMA-MM, and GMA-AF were cut into discs and placed in 48-well plates, followed by irradiation sterilization for 48 h.
[0071] Mouse bone marrow mesenchymal stem cells (BMSCs) were cultured at 5.0×10 4 The cells were seeded on the membrane at a density of 10 cells / ml and cultured in a CO2 incubator at 37°C for 14 days. After culture, the cells were stained with a live / dead staining kit (Biyuntian Biotech) to observe the cell growth status using a confocal laser scanning microscope (CLSM, Nikon A1R). In addition, the lactate dehydrogenase (LDH) detection kit (Biyuntian Biotech) was used to quantify the LDH level in BMSCs cultured on different sample surfaces for 7 days to indicate cell viability.
[0072] Cell adhesion test of GMA-Col: The samples were segmented along their longitudinal axis according to the gradient distribution of mineral content (Ca / Ca+). The mineral deposition of GMA-Col from high to low was zone I (GMA-HM with rich mineral deposition), zone II-a (GMA-MM with moderate mineral deposition), zone II-b (GMA-LM with minimal mineral deposition) and zone III (GMA-AF with no mineral deposition). Circular samples with a diameter of 10 mm were cut from each zone and placed in 48-well plates for cell culture studies. RF-Col and GMA-AF samples were cut into discs with a diameter of 10 mm and sterilized by irradiation in 48-well plates for 48 h.
[0073] Mouse tendon stem cells (TSPC) adhesion: TSPC were plated at 5.0×10 4The cells were seeded on the membrane at a density of 1 cell / ml and cultured at 37°C in a humidified incubator with a 5% CO2 atmosphere for 1 day. The TSPC-seeded material was then fixed in 4% (w / v) paraformaldehyde for 20 minutes and permeabilized in 0.3% (v / v) Triton X-100 for 10 minutes. The cells were stained with a PBS solution of rhodamine-phalloidin for 20 minutes to observe the cytoskeleton, and then stained with a DAPI solution for 15 minutes to mark the nucleus. Wash with PBS for 10 minutes after each step. Cell morphology was observed using a confocal laser scanning microscope (CLSM, Nikon A1R). Image J software was used to semi-quantitatively analyze the cell aspect ratio and area. Image J software was used to measure the orientation, area, and aspect ratio of the cells.
[0074] Tendon differentiation test of mouse tendon stem cells: To study the biological activity of GMA-AF-induced TSPC differentiation, the cells were cultured on RF-Col and GMA-AF, cut into discs with a diameter of 10 mm and attached to the bottom of a 48-well plate. After 14 days of culture, the cells were digested with 0.25% trypsin solution, and mRNA was extracted by TRIzol reagent (Bio-Rad, USA) according to the manufacturer's instructions. The extracted mRNA was reverse transcribed into cDNA by a detection kit (iScript1TM cDNA Bio-Rad kit USA), and RT-PCR was performed using a TB Green detection kit (iTaq Universal SYBR Green, Bio-Rad, USA) according to the manufacturer's protocol. Real-time fluorescence quantitative polymerase chain reaction (qRT-PCR, CFX Opus 384, USA) analyzed the expression of tendon differentiation-related genes (Col 1a1, Scx, Tnmd, Dcn and Tnc). The primer sequences are detailed in Table S1:
[0075] Table S1 Primer sequence I
[0076]
[0077] Chondrogenic differentiation and osteogenic differentiation test of mouse bone marrow mesenchymal stem cells: In order to study the biological activity of GMA-HM, GMA-LM, GMA-MM and GMA-AF in inducing BMSCs differentiation, cells were cultured on these groups for Q-PCR analysis. Each group of GMA-HM, GMA-LM, GMA-MM and GMA-AF was cut into a disc with a diameter of 10 mm and attached to the bottom of a 48-well plate, and then sterilized by irradiation for 48 hours. BMSCs were seeded on the membrane and cultured in a 5% CO2 cell culture incubator at 37°C. After 14 days of culture, the cells were digested with 0.25% trypsin solution, and mRNA was extracted using TRIzol reagent (Bio-Rad, USA). The extracted mRNA was reverse transcribed into cDNA using the iScript1TM cDNA synthesis kit (Bio-Rad, USA), and then real-time PCR (RT-PCR) was performed using TB Green supermix (iTaq Universal SYBR Green Supermix, Bio-Rad, USA) according to the manufacturer's instructions (n = 3). Real-time quantitative polymerase chain reaction (qRT-PCR, CFX Opus 384, USA) was used to analyze the expression of genes related to chondrogenesis (Sox9, Aggrecan, Col II) and osteogenic differentiation (Ocn, Runx, BMP2). The highly purified primer sequences are listed in Table S2:
[0078] Table S2 Primer sequence II
[0079]
[0080] IV. In vivo evaluation of the repair of gradient mineralized highly oriented collagen fiber membranes
[0081] Rabbit infraspinatus tendon giant rotator cuff tear (RCT) model: Surgical instruments were used to release the subcutaneous tissue to expose the infraspinatus tendon and its insertion point on the humeral head. Forceps were used to dissect the infraspinatus tendon from the surrounding soft tissue and cut near the greater tuberosity of the humeral head to form a 7mm×5mm infraspinatus tendon defect. The remaining tendon ends were trimmed, and the residual tendon and cartilage tissue at the insertion point of the infraspinatus tendon on the humeral head were further scraped off with a blade until the subchondral bone was exposed (depth 3mm). The material was implanted and its attachment tissue compatibility, tendon regional regeneration effect, tendon-bone interface regional regeneration effect, and bone regional regeneration effect were investigated. The integration of the host tissue after the material was implanted and the recovery of the damaged attachment tissue structure were further investigated by histological evaluation. The reconstruction of the rotator cuff motion function after the material was implanted was evaluated by animal behavioral tests.
[0082] Quantitative histological scoring criteria for tendon tissue architecture, arrangement and maturation:
[0083] Table S3 Tendon maturity scores
[0084]
[0085]
[0086] Table S4 Modified histological scoring system for evaluating the regenerated tendon-bone interface
[0087]
[0088] From the above results, it can be seen that AHF-Col has an aligned hierarchical fibrous structure and exhibits enhanced mechanical properties in the alignment direction: the mechanical properties of AHF-Col significantly increase with the increase in the degree of orientation, and AHF-Col prepared under 200% strain conditions has the highest tensile strength (95.97±1.6MPa) and Young's modulus (5.06±0.07Gpa) in the dry state. (The strength of natural tendon tissue from different animals varies between 55 and 120MPa).
[0089] Gradient mineral content facilitates spatially continuous variation of mechanical stiffness: Gradient mineral content is essential for natural tendon-to-bone integration and provides a mechanism for spatially continuous variation of mechanical stiffness, thereby eliminating high stresses at the interface and effectively transferring mechanical loads from tendon to bone. Constructing mineral content gradients in implants can not only better adapt to the in vivo transition of mechanical stiffness from tendon to bone, but also has the potential to provide heterogeneous physicochemical cues (e.g., stiffness, composition) for spatial cellular phenotypes, facilitating tendon-to-bone reconstruction. Controlling the infiltration of mineralizing solutions into the scaffold in space and time provides a potential method to generate mineral gradients on AHF-Col. The gradient distribution of HAp within and between fibers in the material can mimic the hierarchical spatial distribution of minerals in bone, ensuring a smooth transition of mechanical properties from relatively flexible soft tissue to rigid hard tissue.
[0090] Differentiated surface morphology, mineral content, stiffness, and wettability of localized regions on GMA-Col affect cell adhesion, proliferation, and differentiation to some extent: different regions of GMA-Col showed good biocompatibility, supporting the adhesion and sustained proliferation of cells associated with tendon and bone healing. In addition, these results may indicate that GMA-Col allows for the provision of different localized physicochemical environments that can spatially selectively promote cell differentiation into tendon, cartilage, or bone, potentially recreating the gradient cell phenotype of tendon-bone interface tissue.
[0091] Implantation of GMA-Col significantly enhanced the mechanical properties of the healed injury site and the recovery of the animals' motor function: the newly formed tendon tissue showed mature collagen expression and organizational arrangement, while the reconstructed attachment tissue formed mature fibrocartilage, showing permeability and tight connection with the regenerated bone tissue. More encouragingly, the implantation of this material significantly enhanced the mechanical properties of the healed injury site and the recovery of the animals' motor function. Overall, this biomimetic implant / patch material has excellent mechanical properties and gradient biological functions, showing great potential for comprehensive regeneration from tendon to bone.
[0092] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0093] Example 1 Preparation and characterization of oriented structural collagen fiber membrane AHF-Cols
[0094] 1) Preparation of electrolyte: 100 mg of type I collagen extracted from pig skin was weighed and dissolved in 10 mL of ultrapure water, glacial acetic acid was added to fully dissolve it, and the final pH of the solution was adjusted to 3.5 to obtain a collagen solution with a concentration of 10 mg / mL. Hydrogen peroxide was added to the solution at a volume ratio of 10:1 between the collagen solution and hydrogen peroxide, and the solution was stirred for 5 minutes to mix evenly, and the bubbles in the solution were removed by centrifugation, and then the electrolyte was stored in an ice-water mixed bath to prevent the decomposition of hydrogen peroxide in the solution due to the high temperature while waiting for use.
[0095] 2) Preparation of collagen gel membrane E-Col by electrochemical deposition technology: A three-electrode system (CHI660E) was used for electroplating, with a titanium sheet (size 2 cm × 3 cm) as the working electrode, a platinum wire as the counter electrode, and Ag / AgCl as the reference electrode. The three-electrode system was inserted into a pre-configured electrolyte and connected to an electrochemical workstation. The experiment used a constant current mode, with a current set to 40 mA (current density 6.67 mA / cm 2 ,), deposition time 3600s. The corresponding electrode reaction is as follows:
[0096] Anode: 2H2O-4e - →4H + +O2;
[0097] Cathode: 2H2O+4e - →4OH - +2H2
[0098] The pH gradient was established by using the electrode reaction described above. After the reaction was completed, the titanium sheet was removed from the electrolyte, and the gel film attached to the titanium sheet was rinsed with ultrapure water to remove excess electrolyte on the surface, and then the gel film E-Col was peeled off from the electrode for subsequent preparation steps.
[0099] 3) Preparation of oriented structure collagen fiber membrane AHF-Cols: Under the action of a mechanical stretching machine, the electrochemically assembled collagen gel membrane E-Col was stretched to different strains along the length direction: 0%, 50%, 100%, 150%, and 200%, so that the structure of the collagen gel membrane was further oriented, and the further oriented network structure was immersed in ethanol to temporarily fix the oriented structure. Subsequently, the stretched collagen gel membrane was immersed in a 0.1M PBS physiological ion environment solution for 2 hours, while continuously loading the two ends of the membrane to maintain the oriented structure. After soaking, the film was placed in an NH3 atmosphere for 24 hours, and external forces were continuously applied at both ends to induce the growth of oriented collagen microfibrils and the formation of D bands, and then dried. The dried collagen membrane was then cross-linked in a glutaraldehyde solution (1% w / v in 90% v / v ethanol-water solution) for 30 minutes, and then repeatedly washed with ultrapure water to remove any residual glutaraldehyde. Finally, AHF-Cols prepared under different tensile strain conditions were obtained, and their structure and mechanical properties were further characterized.
[0100] 4) Microscopic morphology characterization of oriented structured collagen fiber membrane AHF-Cols:
[0101] ① Scanning electron microscopy (SEM, S4800 Hitachi) was used to observe the surface morphology of collagen fiber membranes with different degrees of strain ( Figure 1 cd). Low magnification SEM images ( Figure 1 c) shows that the prepared film surface exhibits a fibrous morphology with different degrees of strain, especially the 200% strained AHF-Col, which shows an aligned fibrous surface with a diameter of about 10 μm along the stretching direction (marked by white arrows). In contrast, the surface of the collagen film of the control group (0% strain, RF-Col) exhibits a relatively random fibrous morphology. High magnification SEM image ( Figure 1 d) further revealed that the fiber surface of all samples was composed of nanoscale fibrils with D-band characteristics (e.g. Figure 1 d as shown in the inset in the lower left corner).
[0102] ② Polarized light microscopy (Axio Scope A1, Germany) was used to study the orientation structure of the sample. For polarized light microscopy, images were taken in cross-polarization mode, with the polarizer (P) and analyzer (A) perpendicular to each other, so that the sample strain axis was at a 45-degree angle to the analyzer and polarizer ( Figure 1 b). Polarized optical microscope image ( Figure 1 b) shows that all AHF-Cols exhibit significant optical birefringence, and more obvious birefringence is observed in AHF-Cols with larger strain, while the collagen film of the control group (0% strain, RF-Col) exhibits weaker birefringence. This result preliminarily indicates that the collagen in AHF-Cols is unidirectionally oriented along the deformation direction.
[0103] ③ Small-angle X-ray scattering (SAXS, BL19U2, China) was used to study the orientation structure of the sample. SAXS is to irradiate the sample with an X-ray beam, with a distance from the sample to the detector of 1950 mm and an exposure time of 60 seconds to obtain the scattered signal. The two-dimensional SAXS data obtained by processing the Fit2D software is used to average the one-dimensional scattering intensity curve as a function of the azimuth angle. The Herman orientation factor (φ) is calculated using the following formula to quantify the arrangement of the collagen fiber network:
[0104]
[0105] Where φ is the azimuth angle, <cos 2 φ> is the average value of the square of the azimuthal cosine, and I(φ) is the one-dimensional scattering intensity at the azimuthal angle φ after subtracting the background intensity. The Herman orientation factor fc ranges from 0 to 1, where the former indicates an isotropic structure and the latter corresponds to a completely unidirectional structure. The larger the value, the higher the degree of orientation ( Figure 1 e). 2D SAXS pattern of RF-Col ( Figure 1 e) shows an almost uniform scattering ring, indicating its isotropic structure, while AHF-Cols exhibit scattering rings with different degrees of stretching, which is consistent with the anisotropic alignment of the fiber structure. The quantitative description of orientation is the Hermann orientation parameter (fc), and their respective fc values are shown in the lower right corner of the 2D SAXS patterns of different samples. RF-Col shows a low degree of alignment (fc = 0.18), while the fc of AHF-Cols increases significantly with increasing strain, reaching a high degree of alignment of 0.94 when the strain of AHF-Col is 200%. These results indicate that the strain caused by mechanical stretching during the preparation process can induce long-range alignment of the fibril structure within the collagen film along the strain direction. In addition, the 2D SAXS patterns of both RF-Col and AHF-Cols show D-band formation (i.e., the characteristic scattering ring in the 2D SAXS pattern).
[0106] ④ All diffraction peaks observed in the SAXS sample can be explained by a single periodic d-band (D), which is calculated according to the Bragg equation:
[0107]
[0108] Where n is the order of peaks 1, 2, 3, etc. q is the position of the peak on the horizontal axis of the 1D SAXS spectrum. Place it on the sample stage and observe its microstructure using small-angle X-ray (SAXS, BL19U2) ( Figure 1 e) The distance between the sample and the detector is 1950 mm. The sample is measured with an X-ray beam for several seconds until the scattered signal intensity reaches 10 5 The scattering data were obtained and the microstructure of collagen fiber membranes with different degrees of strain (i.e., D-band formation, Herman orientation factor) was studied ( Figure 1 f). 2D SAXS images of RF-Col and AHF-Cols ( Figure 1 e) and the corresponding 1D SAXS spectra (q range from 0.2 to 1.2 nm-1, e.g. Figure 1 f) both show evidence of D-band formation (i.e., characteristic scattering rings in the 2D SAXS pattern) and a 64.6 nm D-band scattering peak (calculated by the Bragg equation).
[0109] 5) Evaluation of the mechanical properties of oriented structural collagen fiber membrane AHF-Cols: Collagen gel membranes with different degrees of strain were cut into rectangles and subjected to tensile tests at room temperature. The static tensile properties of the samples at room temperature were measured using a dynamic biomechanical testing system (Electro-3220, USA). The material was cut into rectangular strips (10mm×30mm), and the thickness was measured by an electronic thickness gauge. For static mechanical testing, the stretching rate was set to 0.05mm / s (0.17% / s). The strain of the sample was calculated by dividing the length change at the break by the initial distance between the clamps. The stress is calculated as the force applied to the sample divided by the initial cross-sectional area. The tensile breaking strength and elongation at break of the collagen fiber material samples at different tensile strains were determined by stress-strain curves. Young's modulus is calculated based on the slope of the initial linear region of the stress-strain curve ( Figure 1 gh). AHF-Col has an aligned hierarchical fibrous structure and exhibits enhanced mechanical properties in the aligned direction. Representative stress-strain curves along the orientation ( Figure 1 g) and quantitative comparison of tensile strength and Young's modulus ( Figure 1 h) The effect of different orientation degrees on the mechanical properties of AHF-Col was further emphasized. The results showed that the mechanical properties of AHF-Col significantly improved with the increase of orientation degree, and AHF-Col prepared under 200% strain conditions had the highest tensile strength (95.97±1.6MPa) and Young's modulus (5.06±0.07GPa) in the dry state.
[0110] Figure 1The results showed that AHF-Col with a strain rate of 200% had the best aligned hierarchical fiber structure and the highest mechanical properties. Considering the clear hierarchical arrangement and mechanical strength comparable to native tendon tissue, we selected the highly oriented collagen fiber membrane AHF-Col prepared under 200% strain plastic deformation for subsequent studies.
[0111] Example 2 Preparation and structural characterization of mineralized / highly oriented collagen fiber membrane MAHF-Cols
[0112] 1) Preparation of mineralized / highly oriented collagen fiber membranes MAHF-Cols mineralized with different formulations (Ⅰ-Ⅴ): See Table S5 for the specific formulations. Specifically, the 200% strained AHF-Col prepared in Example 1 was immersed in mineralization precursor solutions of different formulations (as shown in the table below) and mineralized at a constant temperature of 37°C for 7 days. During the entire mineralization process, the mineral solution was replaced every 12 hours to ensure effective mineralization. After the mineralization was completed, all materials were rinsed with ultrapure water to remove unbound mineral components, and then dried overnight in a constant temperature oven at 37°C to obtain the mineralized sample MAHF-Cols.
[0113] Table S5 Mineralization solution formula
[0114]
[0115] 2) The mineral content and structure of the mineralized / highly oriented collagen fiber membrane MAHF-Cols samples mineralized with different formulas (Ⅰ-Ⅴ) were further characterized to screen out the best mineralization formula Ⅴ for subsequent experiments.
[0116] ① Thermogravimetric analysis (TGA) was performed using a thermogravimetric analyzer (TG209F1, Germany) to determine the residual mass and calculate the mineral content in different MAHF-Col samples. The heating process was carried out at a nitrogen flow rate of 20 ml / min, and the temperature was increased from 20°C to 800°C at a rate of 10°C / min. Figure 8 c)( Fig. 9 a) The results show that the MAHF-Col prepared using Formula V has the highest inorganic mineral content, accounting for about 53% of the total weight, which is slightly lower than the proportion of inorganic matter in natural bone (about 65%).
[0117] ②Using Cu Kα radiation XRD analysis was performed with the voltage and current set to 40 kV and 40 mA, respectively. The scanning range was from 10° to 60°, and the scanning rate was 10° / min. The crystal structure of the minerals in the mineralized collagen fiber membrane was analyzed using an X-ray diffractometer (Max2550VB, Japan). The X-ray diffraction (XRD) spectrum of the mineralized collagen membrane was obtained, and the mineral crystal structure was analyzed using Jade software based on the XRD spectrum. By comparing the results with the standard hydroxyapatite (HAP) PDF card, the crystalline phase present in the sample can be identified ( Figure 8 d). The crystallinity of mineral components in different samples was calculated using Jade software. Fig. 9 b) The results show that the MAHF-Col obtained from formula V exhibits the strongest HAp characteristic crystal diffraction peak.
[0118] Therefore, the present invention selected mineralization formula V to prepare mineralized / highly oriented collagen fiber membrane MAHF-Col for subsequent research.
[0119] Example 3: Comparison of mineralized / highly oriented collagen fiber membrane MAHF-Col mineralized using mineralization formula V and high oriented collagen fiber membrane AHF-Col before mineralization
[0120] 1) Preparation of mineralized / highly oriented collagen fiber membrane MAHF-Col mineralized by mineralization formula V: The 200% strain AHF-Col prepared in Example 1 was mineralized by mineralization formula V. Specifically, the 200% strain AHF-Col prepared in Example 1 was immersed in the mineralization precursor solution of formula V [Solution A: CaCl2·2H2O (0.1M, 10mL) + pAsp (polyaspartic acid, molecular weight of about 10000, 0.3g); Solution B: Na2HPO4 (0.1M, 10mL) + PAA (polyacrylic acid, molecular weight of about 2000, 0.6g); Solution A and Solution B were mixed evenly and the pH value was adjusted to 7.4 using NaOH solution], and mineralized at a constant temperature of 37°C for 7 days. During the entire mineralization process, the mineral solution was replaced every 12 hours to ensure effective mineralization. After mineralization was completed, all materials were rinsed with ultrapure water to remove unbound mineral components and then dried in a constant temperature oven at 37 °C overnight to obtain the mineralized sample MAHF-Col.
[0121] 2) Comparison of the structure and physicochemical properties of the mineralized / highly oriented collagen fiber membrane MAHF-Col and the highly oriented collagen fiber membrane AHF-Col using mineralization formula V:
[0122] ① Polarized light microscopy (Axio Scope A1, Germany) was used to study the orientation structure and mineral crystal distribution of the samples. For polarized light microscopy, images were taken in cross-polarization mode, with the polarizer (P) and analyzer (A) perpendicular to each other, so that the sample strain axis was at a 45-degree angle to the analyzer and polarizer ( Figure 8 e). Polarized optical microscope image ( Figure 8 e) shows that MAHF-Col still exhibits significant optical birefringence, indicating that its long-range orientation structure still exists after mineralization.
[0123] ② The samples were freeze-dried until completely dry, and then the surface morphology was analyzed using a field emission scanning electron microscope (SEM, HeliosG4 UC, USA). Specifically, the samples were mounted on a flat stub with conductive tape and sputter-coated with gold for 30 seconds at an accelerating voltage of 15 kV using an ion sputtering instrument ( Figure 8 f). SEM image ( Figure 8 f) A more intuitive display of the oriented fibrous structure on the surface of MAHF-Col (indicated by the red box). In addition, the formation of minerals in certain areas of the surface of MAHF-Col was observed (indicated by the blue box).
[0124] ③ Use atomic force microscopy (AFM, MFP-3D, UK) to perform high-resolution surface scanning. During the scanning process, a microprobe is used to detect the surface topology and mechanical properties, and the surface height and modulus information at each location are recorded ( Figure 8 k). In addition, the biomineralization process significantly increased the hardness of the samples ( Figure 8 k, surface modulus measured using AFM).
[0125] ④ A transmission electron microscope (TEM, JEM-2100, Japan) was used to observe the fiber morphology and mineral distribution within the sample. The sample was dehydrated in a graded ethanol series, embedded in Eponate 12 resin (Ted Pella, Redding, CA), and cut into slices with a thickness of 60-90 nm, which were placed on a bare copper grid. Imaging was performed at an accelerating voltage of 120 kV ( Figure 8 g). Using transmission electron microscopy (TEM) to observe the MAHF-Col sample sections without osmium acid or uranyl acetate staining, a large number of dark areas were observed ( Figure 8 g), which is mainly due to the large amount of HAp deposited inside MAHF-Col because HAp has strong electron scattering ability. In contrast, unstained non-mineralized collagen materials usually show low contrast in TEM images.
[0126] ⑤ The chemical composition and structure of MAHF-Col were characterized by attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR, Nicolet iS50, USA). The sample was placed directly on the ATR crystal and infrared light was irradiated directly onto the sample surface. The area in contact with the ATR crystal absorbed the infrared light, thus producing a specific absorption signal. The ATR-FTIR scanning range was 4000-400cm -1 , resolution 2cm -1 ( Figure 8 h). Fourier transform infrared spectroscopy (FTIR, Figure 8 h) The results show that AHF-Col has a characteristic absorption peak corresponding to the amide bond of collagen, while MAHF-Col exhibits not only the characteristic absorption peak of collagen but also the characteristic absorption peak of HAp. Specifically, 568 cm -1 The absorption peak at is attributed to PO4 3- ν4 bending mode, which splits into two smaller peaks due to the crystallization of HAp. 1053cm -1 The absorption peak at is attributed to PO4 3- The ν3 antisymmetric stretching mode.
[0127] ⑥Using Cu Kα radiation XRD analysis was performed with the voltage and current set to 40 kV and 40 mA, respectively. The scanning range was 10° to 60°, and the scanning rate was 10° / min. The crystal structure of the minerals in the mineralized collagen fiber membrane was analyzed using an X-ray diffractometer (Max2550VB, Japan). The X-ray diffraction (XRD) spectrum of the mineralized collagen membrane was obtained, and the mineral crystal structure was analyzed based on the XRD spectrum using Jade software ( Figure 8 i). X-ray diffraction ( Figure 8 i) The presence of HAp in MAHF-Col was also further confirmed.
[0128] ⑦ Use a contact angle meter (JC2000D3) to characterize the hydrophilic and hydrophobic properties. Place the sample on the test bench, drop 10 μL of ultrapure water on the surface of the material, and measure the contact angle between the material surface and the water droplet ( Figure 8 j). In addition, the biomineralization process significantly improved the wettability and hardness of the samples. Compared with AHF-Col, MAHF-Col has a stronger hydrophilicity ( Figure 8 j).
[0129] ⑧The static tensile properties of the samples at room temperature were measured using a dynamic biomechanical testing system (Electro-3220, USA). The material was cut into rectangular strips (10 mm × 30 mm), and the thickness was measured by an electronic thickness gauge. For static mechanical testing, the stretching rate was set to 0.05 mm / s (0.17% / s). The strain of the sample was calculated by dividing the change in length at break by the initial distance between the clamps. The stress was calculated as the force applied to the sample divided by the initial cross-sectional area. The tensile breaking strength and elongation at break of the collagen fiber material samples at different tensile strains were determined by stress-strain curves. Young's modulus was calculated based on the slope of the initial linear region of the stress-strain curve ( Figure 8 ln). Representative stress-strain curve ( Figure 8 l) and quantitative results ( Figure 8 m) showed that the strength of MAHF-Col was significantly improved compared with AHF-Col, while the fracture strain was not significantly reduced, indicating that the biomimetic mineralization of AHF-Col did not increase its brittleness. This is a valuable property for organic-inorganic mineral composites. It is speculated that the composite of nanoscale HAp and collagen fibers reduces the possibility of material fracture due to stress concentration at the organic-inorganic mineral interface. In addition, biomimetic mineralization significantly enhanced the Young's modulus and toughness of the material ( Figure 8 n). The Young's modulus of MAHF-Col is close to 7 GPa, which is close to the Young's modulus of natural bone tissue (cancellous bone ranges from 3-8 GPa), which may enhance the mechanical compatibility with bone tissue.
[0130] Figure 8 The results showed that the biomimetic mineralization of AHF-Col not only retained its inherent long-range multi-level oriented fiber structure, but also the nanoscale composite of collagen matrix and HAp could maximize the comprehensive mechanical properties of MAHF-Col and mimic the physicochemical properties of local bone sites.
[0131] Example 4 Preparation and characterization of gradient mineralized highly oriented collagen fiber membrane GMA-Col
[0132] 1) Preparation of gradient mineralized highly oriented collagen fiber membrane GMA-Col: According to the mineralization solution formula V [Solution A: CaCl2·2H2O (0.1M) + pAsp (polyaspartic acid, molecular weight of about 10000, 0.03g / ml); Solution B: Na2HPO4 (0.1M) + PAA (polyacrylic acid, molecular weight of about 2000, 0.06g / ml); equal volumes of solution A and solution B are mixed evenly and the pH value is adjusted to 7.4 using NaOH solution], the mineralization solution is prepared. The 200% strain highly oriented collagen fiber membrane AHF-Col prepared in Example 1 is placed vertically at the bottom of a beaker, and then the prepared mineral solution is loaded into a 10mL plastic syringe, and the solution is continuously injected into the beaker at a speed of 0.5ml / h using a syringe pump, and mineralized at a constant temperature of 37°C for 7 days. During the entire mineralization process, the mineralization solution in the syringe pump is replaced every 12 hours to ensure the mineralization effect. As the mineral solution is gradually added to the beaker, the minerals are gradually deposited on the highly oriented collagen fiber membrane AHF-Col immersed in the solution. As the level of the mineral solution in the beaker rises, a gradient of mineral content is formed due to the different immersion times at the upper and lower ends of the highly oriented collagen fiber membrane AHF-Col. After the mineralization is completed, the material is rinsed with ultrapure water to remove excess mineralization liquid on the surface, and then placed in a 37°C electric constant temperature blast furnace overnight for drying. The resulting highly oriented / gradient mineralized collagen fiber membrane is named GMA-Col. ( Figure 2 a)
[0133] 2) Gradient structure characterization of gradient mineralized highly oriented collagen fiber membrane GMA-Col:
[0134] ① The prepared highly oriented / gradient mineralized collagen fiber membrane GMA-Col was immersed in an Alizarin Red solution (40mM) for 3 hours, and then the surface of the material was thoroughly washed with ultrapure water to remove residual dyes. After air drying, macroscopic photos of GMA-Col were taken using a digital camera. AHF-Col (total length of 10mm) was vertically fixed in a container parallel to its alignment direction, and the mineralization solution was dripped at a constant rate every day using a syringe pump. As the liquid level increased, the 7mm length range of AHF-Col (from bottom to top) experienced continuous penetration of different durations every day (Note: the bottom and 7mm height areas correspond to the longest and shortest penetration times, respectively), as shown in Figure 2. Figure 2a. Since mineral deposition is positively correlated with the penetration time of the mineralizing solution, a mineral content gradient can be generated along the orientation direction of AHF-Col, thereby constructing a gradient mineralized AHF-Col (referred to as "GMA-Col"). In order to confirm the presence of gradient mineral components in GMA-Col, the present invention first dyed GMA-Col with Alizarin Red S (ARS, which chelates with calcium ions to form a red complex). The dyed GMA-Col shows a gradient red change along the long axis (i.e., the orientation direction) ( Figure 2 b), preliminarily confirming the gradient content variation of sedimentary minerals along the GMA-Col orientation direction.
[0135] ② Scanning electron microscopy (SEM, Helios G4 UC) was used to examine the morphology of mineral crystals deposited at different positions along the long axis of GMA-Col. SEM images of different areas at low and high magnifications ( Figure 2 cd) show that the three regions of GMA-Col exhibit different degrees of mineral formation on the surface. The surface of region I on GMA-Col is almost completely covered with a large number of clustered minerals, while the surface of region II shows a clear mineral gradient distribution. The area near region I (defined as "II-a", marked by an orange box) has relatively more mineral crystals (indicated by orange arrows), while the area near region III (defined as "II-b", marked by a yellow box) has only a few mineral crystals (indicated by yellow arrows). The unmineralized surface of region III on GMA-Col is smooth, and high-magnification SEM images further reveal its aligned fibrous surface morphology.
[0136] ③ Energy dispersive spectroscopy (EDS) was used to observe the distribution of Ca and P elements in different regions. At the same time, X-ray energy dispersive spectroscopy (EDS) was used to determine the elemental composition and distribution at different positions along the long axis of GMA-Col to obtain the Ca / (Ca+C) atomic ratio. Figure 2 e The results show that there is a downward trend from zone I to zone III, and the content of Ca and P elements in zone II shows an obvious gradient change. Figure 2 h further confirmed that the atomic ratio of Ca to (Ca+C) gradually decreased from bottom to top along the axial direction (i.e., orientation direction). In the area near the bottom, this ratio was as high as ≈80%, while no calcium was detected in the area near the top. This trend in calcium content indicates a composition gradient of the mineral, confirming the spatial gradient distribution of HAp in GMA-Col.
[0137] ④ Transmission electron microscopy (TEM, JEM-2100) was used to observe the spatial morphology of collagen fibers and deposited mineral crystals in GMA-Col. TEM images of different regions of GMA-Col without osmium acid or uranyl acetate staining ( Figure 2f) further reveals the difference in the degree of mineralization within it. The completely dark area observed in region I indicates that it is highly mineralized. The mineralized area (observed dark area) from region II-a to region II-b is significantly reduced, indicating that the internal mineralization degree gradually decreases. In the unmineralized region III, no obvious dark area indicating the formation of HAp was observed.
[0138] ⑤ The GMA-Col surface was scanned at high resolution using an atomic force microscope (AFM, MFP-3D) to obtain the morphological characteristics of the sample surface, and the surface modulus at four locations along the GMA-Col mineral gradient was measured. The surface modulus at different locations in GMA-Col was further examined using an atomic force microscope (AFM). The results showed that the modulus of different regions decreased with increasing mineral content, such as Figure 2 As shown in g. Figure 2 The quantitative data in Figure 1 show that the local modulus of GMA-Col decreases with decreasing mineral content, from approximately 15 GPa to approximately 7 GPa, as the mineralization gradient (i.e., alignment direction) decreases. This mechanical property gradient is critical for mitigating stress concentrations at interfaces between dissimilar materials, such as connective soft tissue and bone.
[0139] ⑥ Use a contact angle meter (JC2000D3) to characterize the hydrophilic and hydrophobic properties of GMA-Col. Place GMA-Col on the test bench, drop 10 μL of ultrapure water on different positions on the material surface, and measure the contact angle between the material surface and the water droplet. Figure 2 j further illustrates the gradient wettability of GMA-Col, where local mineralization promotes the increase of local hydrophilicity.
[0140] Overall, these results indicate that in GMA-Col, there is a gradient in the content of HAp both inside and outside the fiber, resulting in a gradient change in surface stiffness and wettability.
[0141] Example 5 Cytocompatibility of Gradient Mineralized Highly Oriented Collagen Fiber Membrane GMA-Col
[0142] 1) Preparation of gradient mineralized highly oriented collagen fiber membrane GMA-Col: According to the mineralization solution formula V [Solution A: CaCl2·2H2O (0.1M) + pAsp (polyaspartic acid, molecular weight of about 10000, 0.03g / ml); Solution B: Na2HPO4 (0.1M) + PAA (polyacrylic acid, molecular weight of about 2000, 0.06g / ml); equal volumes of solution A and solution B are mixed evenly and the pH value is adjusted to 7.4 using NaOH solution], the mineralization solution is prepared. The 200% strain highly oriented collagen fiber membrane AHF-Col prepared in Example 1 is placed vertically at the bottom of a beaker, and then the prepared mineral solution is loaded into a 10mL plastic syringe, and the solution is continuously injected into the beaker at a speed of 0.5ml / h using a syringe pump, and mineralized at a constant temperature of 37°C for 7 days. During the entire mineralization process, the mineralization solution in the syringe pump is replaced every 12 hours to ensure the mineralization effect. As the mineral solution is gradually added to the beaker, the minerals are gradually deposited on the highly oriented collagen fiber membrane AHF-Col immersed in the solution. As the level of the mineral solution in the beaker rises, a gradient of mineral content is formed due to the different immersion times at the upper and lower ends of the highly oriented collagen fiber membrane AHF-Col. After the mineralization is completed, the material is rinsed with ultrapure water to remove excess mineralization liquid on the surface, and then placed in a 37°C electric constant temperature blast furnace overnight for drying. The resulting highly oriented / gradient mineralized collagen fiber membrane is named GMA-Col.
[0143] 2) Evaluation of the cell compatibility of the gradient mineralized highly oriented collagen fiber membrane GMA-Col
[0144] To investigate the cytocompatibility of GMA-Col, the samples were segmented along their longitudinal axis according to the gradient distribution of mineral content (Ca / Ca+C). The mineral deposition of GMA-Col from high to low was zone I (GMA-HM with rich mineral deposition), zone II-a (GMA-MM with moderate mineral deposition), zone II-b (GMA-LM with minimal mineral deposition), and zone III (GMA-AF with no mineral deposition). Circular samples with a diameter of 10 mm were cut from each zone and placed in 48-well plates for cell culture studies. GMA-HM, GMA-LM, GMA-MM, and GMA-AF were cut into discs and placed in 48-well plates, followed by irradiation sterilization for 48 h.
[0145] ① Mouse tendon stem cell (TSPC) adhesion test: RF-Col and GMA-AF samples were cut into circles with a diameter of 10 mm and sterilized by irradiation in a 48-well plate for 48 hours. TSPC were plated at 5.0×10 4The density of cells / ml was inoculated onto the membrane and cultured at 37°C in a humidified incubator with a 5% CO2 atmosphere for 1 day. The material inoculated with TSPC was then fixed in 4% (w / v) paraformaldehyde for 20 minutes and permeabilized in 0.3% (v / v) Triton X-100 for 10 minutes. The cells were stained with a PBS solution of rhodamine-phalloidin for 20 minutes to observe the cytoskeleton, and then stained with a DAPI solution for 15 minutes to mark the nucleus. Wash with PBS for 10 minutes after each step. Cell morphology was observed using a confocal laser scanning microscope (CLSM, Nikon A1R). Image J software was used to semi-quantitatively analyze the cell aspect ratio and area. Image J software was used to measure the orientation, area, and aspect ratio of the cells. Figure 3 The confocal fluorescence images in a and 3b show the differentiated adhesion morphologies of TSPCs on GMA-AF and RF-Col 24 hours after seeding, respectively. TSPCs on RF-Col exhibited an isotropic star-shaped morphology, while TSPCs on GMA-AF exhibited a stretched state and an elongated spindle shape. The statistical quantitative data of the confocal fluorescence images on the right side of each group further confirmed that TSPCs on GMA-AF exhibited significantly directional arrangement and distribution compared with the isotropic arrangement and distribution of TSPCs on RF-Col. Subsequently, the cell aspect ratio and area were quantitatively analyzed using the actin-stained cytoskeleton to further quantify the cell elongation rate. Figure 3 As shown in c, the aspect ratio of TSPCs on GMA-AF reached nearly 14, which was significantly higher than 1.85±0.18 on RF-Col. Figure 3 All these data indicate that TSPCs can sense and respond to the aligned fiber morphology on GMA-AF after initial attachment, and these aligned GMA-AF fiber morphologies can induce the elongated cell shape of TSPCs.
[0146] ② Mouse bone marrow mesenchymal stem cells (BMSC) cell viability test: Mouse bone marrow mesenchymal stem cells (BMSC) were cultured at 5.0×10 4 The cells were seeded onto the membrane at a density of 10 cells / ml and cultured in a CO2 incubator at 37°C for 14 days. After culture, the cells were stained with a live / dead staining kit (Biyotime Biotech) to observe the cell growth status using a confocal laser scanning microscope (CLSM, Nikon A1R). In addition, the lactate dehydrogenase (LDH) detection kit (Biyotime Biotech) was used to quantify the LDH level in BMSCs cultured on different sample surfaces for 7 days to indicate cell viability. After culturing the cells in proliferation medium for 7 days, the cell viability on different samples was visually observed by live / dead staining, as shown in Figure 2. Figure 3f. The results showed that all sample surfaces were covered with a large number of living cells (stained green), and no obvious dead cells (stained red) were observed. Quantitative data further showed that BMSCs maintained high cell viability after 7 days of culture on different sample surfaces ( Figure 3 g).
[0147] Example 6 Biological activity of gradient mineralized highly oriented collagen fiber membrane GMA-Col
[0148] 1) Preparation of gradient mineralized highly oriented collagen fiber membrane GMA-Col: According to the mineralization solution formula V [Solution A: CaCl2·2H2O (0.1M) + pAsp (polyaspartic acid, molecular weight of about 10000, 0.03g / ml); Solution B: Na2HPO4 (0.1M) + PAA (polyacrylic acid, molecular weight of about 2000, 0.06g / ml); equal volumes of solution A and solution B are mixed evenly and the pH value is adjusted to 7.4 using NaOH solution], the mineralization solution is prepared. The 200% strain highly oriented collagen fiber membrane AHF-Col prepared in Example 1 is placed vertically at the bottom of a beaker, and then the prepared mineral solution is loaded into a 10mL plastic syringe, and the solution is continuously injected into the beaker at a speed of 0.5ml / h using a syringe pump, and mineralized at a constant temperature of 37°C for 7 days. During the entire mineralization process, the mineralization solution in the syringe pump is replaced every 12 hours to ensure the mineralization effect. As the mineral solution is gradually added to the beaker, the minerals are gradually deposited on the highly oriented collagen fiber membrane AHF-Col immersed in the solution. As the level of the mineral solution in the beaker rises, a gradient of mineral content is formed due to the different immersion times at the upper and lower ends of the highly oriented collagen fiber membrane AHF-Col. After the mineralization is completed, the material is rinsed with ultrapure water to remove excess mineralization liquid on the surface, and then placed in a 37°C electric constant temperature blast furnace overnight for drying. The resulting highly oriented / gradient mineralized collagen fiber membrane is named GMA-Col.
[0149] 2) Tendon differentiation test of mouse tendon stem cells: In order to study the biological activity of GMA-AF in inducing TSPC differentiation, the cells were cultured on RF-Col and GMA-AF, respectively, cut into circles with a diameter of 10 mm and attached to the bottom of a 48-well plate. After 14 days of culture, the cells were digested with 0.25% trypsin solution, and mRNA was extracted by TRIzol reagent (Bio-Rad, USA) according to the manufacturer's instructions. The extracted mRNA was reverse transcribed into cDNA by a detection kit (iScript1TM cDNA Bio-Rad kit USA), and RT-PCR was performed using a TB Green detection kit (iTaq Universal SYBR Green, Bio-Rad, USA) according to the manufacturer's protocol. Real-time fluorescence quantitative polymerase chain reaction (qRT-PCR, CFX Opus 384, USA) was used to analyze the expression of tendon differentiation-related genes (Col 1a1, Scx, Tnmd, Dcn and Tnc). The primer sequences are detailed in Table S1. As shown in Figure 3 As shown in Figure e, after culturing TSPCs on GMA-AF and RF-Col for 14 days, the elongated cells cultured on GMA-AF produced higher mRNA expression levels of tendon-related genes. Specifically, Col 1a1, Scx, Tnmd, Dcn, and Tnc were upregulated 4-10 times compared with the RF-Col group. In summary, gene expression confirmed that GMA-AF with aligned fiber structure can regulate cell shape and further promote the tendon differentiation of TSPCs.
[0150] Example 7 Biological activity of gradient mineralized highly oriented collagen fiber membrane GMA-Col
[0151] 1) Preparation of gradient mineralized highly oriented collagen fiber membrane GMA-Col: According to the mineralization solution formula V [Solution A: CaCl2·2H2O (0.1M) + pAsp (polyaspartic acid, molecular weight of about 10000, 0.03g / ml); Solution B: Na2HPO4 (0.1M) + PAA (polyacrylic acid, molecular weight of about 2000, 0.06g / ml); equal volumes of solution A and solution B are mixed evenly and the pH value is adjusted to 7.4 using NaOH solution], the mineralization solution is prepared. The 200% strain highly oriented collagen fiber membrane AHF-Col prepared in Example 1 is placed vertically at the bottom of a beaker, and then the prepared mineral solution is loaded into a 10mL plastic syringe, and the solution is continuously injected into the beaker at a speed of 0.5ml / h using a syringe pump, and mineralized at a constant temperature of 37°C for 7 days. During the entire mineralization process, the mineralization solution in the syringe pump is replaced every 12 hours to ensure the mineralization effect. As the mineral solution is gradually added to the beaker, the minerals are gradually deposited on the highly oriented collagen fiber membrane AHF-Col immersed in the solution. As the level of the mineral solution in the beaker rises, a gradient of mineral content is formed due to the different immersion times at the upper and lower ends of the highly oriented collagen fiber membrane AHF-Col. After the mineralization is completed, the material is rinsed with ultrapure water to remove excess mineralization liquid on the surface, and then placed in a 37°C electric constant temperature blast furnace overnight for drying. The resulting highly oriented / gradient mineralized collagen fiber membrane is named GMA-Col.
[0152] 2) Chondrogenic differentiation and osteogenic differentiation test of mouse bone marrow mesenchymal stem cells: In order to study the biological activity of GMA-HM, GMA-LM, GMA-MM and GMA-AF in inducing BMSCs differentiation, cells were cultured on these groups for Q-PCR analysis. Each group of GMA-HM, GMA-LM, GMA-MM and GMA-AF was cut into a disc with a diameter of 10 mm and attached to the bottom of a 48-well plate, and then sterilized by irradiation for 48 hours. BMSCs were seeded on the membrane and cultured in a 5% CO2 cell culture incubator at 37°C. After 14 days of culture, the cells were digested with 0.25% trypsin solution, and mRNA was extracted using TRIzol reagent (Bio-Rad, USA). The extracted mRNA was reverse transcribed into cDNA using the iScript1TM cDNA synthesis kit (Bio-Rad, USA), and then real-time PCR (RT-PCR) was performed using TB Green supermix (iTaq Universal SYBR Green Supermix, Bio-Rad, USA) according to the manufacturer's instructions. Real-time quantitative polymerase chain reaction (qRT-PCR, CFX Opus 384, USA) was used to analyze the expression of genes related to chondrogenesis (Sox9, Aggrecan, Col II) and osteogenic differentiation (Ocn, Runx, BMP2). The highly purified primer sequences are listed in Table S2. The results showed that BMSCs seeded on GMA-LM showed the highest mRNA expression levels of three chondrogenesis-related genes, Sox9, Aggrecan, and Col-II, among all groups ( Figure 3 m), indicating that GMA-MM was the best in inducing chondrogenic differentiation of BMSCs. In contrast, among all groups, BMSCs on GMA-HM had the highest mRNA expression levels in three osteogenesis-related genes, Ocn, Runx, and BMP2 ( Figure 3 n).
[0153] The results of Example 6 and Example 7 indicate that GMA-Col allows providing different local physicochemical environments, which can selectively promote cell differentiation into tendon, cartilage or bone in space, thereby potentially reconstructing the gradient cell phenotype of tendon and bone interface tissue.
[0154] Example 8
[0155] Gradient mineralized highly oriented collagen fiber membrane GMA-Col repairs damaged tendon-bone tissue in vivo
[0156] 1) Establishment of the rabbit infraspinatus tendon giant rotator cuff tear (RCT) model: Adult New Zealand white rabbits were used in this experiment. All rabbits and related anesthetics were provided by Shanghai Jiao Tong University Agricultural and Life Science Practice Field Co., Ltd. All procedures and postoperative care protocols were approved by the Institutional Animal Ethics Committee and strictly followed the guidelines for the use and care of animals in research. A total of 96 adult male New Zealand rabbits weighing 2.8±0.2kg were randomly divided into 4 groups: control group implanted with PET (n=24), RF-Col implanted group (n=24), AHF-Col implanted group (n=24) and GMA-Col implanted group (length 10mm, including 7mm non-mineralized GMA-AF area and 3mm mineralized GMA-Ms area, n=24). Initially, a mixture of Cetirizine (tiletamine hydrochloride) and xylazine hydrochloride was prepared in a ratio of 8:1 as an anesthetic for rabbits and administered at 0.3ml / kg body weight. After successful anesthesia, the hair was carefully shaved at the marked site of the shoulder joint of the left forelimb and disinfected with iodine solution. After laying the surgical drape, the acromion landmark of the rabbit was identified and the position of the infraspinatus muscle was determined. A longitudinal incision was made along the axis of the infraspinatus muscle, and the skin was dissected sequentially. Surgical instruments were used to release the subcutaneous tissue to expose the infraspinatus tendon and its insertion point on the humeral head. Forceps were used to dissect the infraspinatus tendon from the surrounding soft tissue and incised near the greater tuberosity of the humeral head to form a 7 mm × 5 mm infraspinatus tendon defect. The remaining tendon end was trimmed, and the residual tendon and cartilage tissue at the insertion point of the infraspinatus tendon on the humeral head were further scraped with a blade until the subchondral bone was exposed (depth 3 mm). The composite patch was sutured and fixed to the remaining infraspinatus tendon end. Two parallel bone tunnels were created at the insertion area of the infraspinatus tendon on the lateral side of the humeral head. The suture at the distal end of the patch was passed through the bone tunnel and tied to fix the patch to the insertion area of the infraspinatus tendon on the humeral head. The surgical site was irrigated with normal saline, and the dissected muscle layer and skin were sutured layer by layer. Three disinfection procedures were implemented at the skin incision site. To prevent postoperative infection, the rabbits were injected intramuscularly with penicillin three days after surgery. After surgery, the rabbits were allowed to move freely in the cage and had free access to water and food. The implanted materials were examined for their attachment tissue compatibility, tendon area regeneration effect, tendon-bone interface area regeneration effect, and bone area regeneration effect. The integration of the host tissue after the implantation of the materials and the recovery of the damaged attachment tissue structure were further examined by histological evaluation. The reconstruction of the rotator cuff movement function after the implantation of the materials was evaluated by animal behavioral tests. ( Figure 4 a)
[0157] 2) GMA-Col repairs the histological structure of tendon tissue at the injured site
[0158] ① The experimental rabbits were euthanized at 4, 8, and 12 weeks after surgery, and gross photographs of the rotator cuff tendon-humerus complex were taken. The rotator cuff tendon-humerus complex samples were fixed in 4% (w / v) paraformaldehyde for 48 hours and decalcified in EDTA solution for 1 month. The completely decalcified samples were dehydrated in a gradient ethanol series (30%–100%), infiltrated with xylene, and embedded in paraffin. 5 μm thick sections were cut along the tendon to bone direction, and the tissue sections were subjected to H&E staining and immunohistochemical staining of type I and type III collagen to observe the expression of collagen in the repair tissue and evaluate the maturity of the regenerated tendon. In addition, Image J software was used to measure and calculate the percentage of positive areas in immunohistochemical staining micrographs of type I and type III collagen. The quantitative histological scoring criteria for tendon tissue structure, arrangement, and maturity are shown in Table S3 and were used to evaluate the tissue quality of each group.
[0159] ②Hematoxylin and eosin (H&E) staining ( Figure 4 b) shows that the implants in each group remained relatively intact and not completely degraded at 4 and 8 weeks after surgery, and the remaining implants (marked with "M") are shown in the lower left corner of the low-magnification slice image. The results 4 weeks after surgery showed that compared with the control group, the control group had less new tissue formation and obvious inflammatory cell infiltration, while the three groups implanted with collagen-based materials had more new tissue formation and less inflammatory cell infiltration. It is worth noting that compared with the RF-Col group, the shape and alignment of the newly formed tendon tissue near the implanted AHF-Col and GMA-Col were more regular (in the direction of the yellow arrow). By the 8th week, the regularly arranged tissue observed in the AHF-Col and GMA-Col groups was denser, while the tissue in the RF-Col group showed irregular arrangement.
[0160] ③Immunohistochemical staining of type I and type III collagen ( Figure 4 c and 4d) and the corresponding quantitative results ( Figure 4 f and 4g) to evaluate the maturity of the newly formed tendon tissue in each group. The results showed that the expression levels of type I and type III collagen in each group of patients at different time points were different, and there was a trend of change over time. At 4 weeks after surgery, the expression of type III collagen in each group was more significant than that of type I collagen. At 8 weeks after surgery, the expression of type III collagen was significantly decreased in the RF-Col group, AHF-Col group, and GMA-Col group, accompanied by an increase in the expression of type I collagen. It is worth noting that higher levels of type I collagen were observed in the AHF-Col and GMA-Col groups compared with the other groups, which may further indicate that the newly formed tendon tissue in these two groups is more mature.
[0161] ④ Immunofluorescence staining was used to detect the expression of glycoprotein Tenascin-C (TNC), which is considered to be a marker of mature tendon tissue. Figure 4As shown in Figure 5e, the expression degree of TNC in each group was different. At 4 weeks, slight TNC secretion was observed in the RF-Col, AHF-Col, and GMA-Col groups compared with the control group. As the repair time prolonged, significant accumulation of TNC was observed in the aligned fibrous tissues of the AHF-Col and GMA-Col groups at 8 weeks (quantitative data are shown in Figure 5e). Figure 4 h), possibly indicating enhanced tendon regeneration in these groups.
[0162] ⑤ According to the tendon tissue maturity scoring criteria (Table S3), combined with the above histological examination, the newly formed tendon tissues in different groups were scored. Compared with the control group and the RF-Col group, the AHF-Col group and the GMA-Col group showed the highest tendon maturity at 8 weeks ( Figure 4 i).
[0163] 3) GMA-Col repairs the histological structure of the tendon-bone interface tissue at the injured site
[0164] ① Rabbits were euthanized at 4, 8, and 12 weeks after surgery, and gross photographs of the rotator cuff tendon-humerus complex were taken. The rotator cuff tendon-humerus complex samples were fixed in 4% (w / v) paraformaldehyde for 48 h and decalcified in EDTA solution for 1 month. The completely decalcified samples were dehydrated in a graded ethanol series (30%–100%), infiltrated with xylene, and embedded in paraffin. 5-μm-thick sections were cut along the tendon-to-bone direction, and the tissue sections were stained with H&E and safranine-o-fast green. The stained sections were observed under an optical microscope, and histopathological images were captured with a digital camera. According to the results of safranine-o-fast green staining, the proportion of fibrocartilage tissue at the tendon-bone interface was measured and calculated by Image J. In addition, the sections were immunofluorescently stained with BMP 2 antibodies for osteoblasts and Aggrecan antibodies for chondrocytes (Shanghai Jiajun Biotechnology, China).
[0165] ②Use H&E staining ( Figure 5 a) Preliminary observation of the histological morphology of the interface area (marked as "I") between the tendon tissue (marked as "T") and the bone tissue (marked as "B", with the bone interface indicated by a blue dotted line) in each group. The results showed that as the repair period prolonged, the complete formation of the interface tissue could be observed at 12 weeks. Compared with the control group, the three groups implanted with RF-Col, AHF-Col, and GMA-Col had smoother and more continuous connections from tendon tissue to bone.
[0166] ③ (SO-FG) staining was used to evaluate the regeneration of fibrocartilage at the interface. Figure 5As shown in b, the red area shows that the fibrocartilage tissue in the RF-Col group, AHF-Col group, and GMA-Col group was significantly larger than that in the control group at different time points, and the area of newly formed fibrocartilage at the interface increased over time. At 8 weeks after surgery, the fibrocartilage in each group showed heterogeneous and immature morphology, and at 12 weeks after surgery, the fibrocartilage tissue structure in each group was mature and relatively complete. Figure 5 Semi-quantitative analysis of d further showed that 8 weeks after surgery, the area of fibrocartilage formation in the GMA-Col group was higher than that in the other groups (P<0.05), and as the repair period prolonged, the difference in fibrocartilage formation between the GMA-Col group and the other groups further increased.
[0167] ④ Immunofluorescence staining was used to detect the expression of Aggrecan and BMP-2 at the interface (TBI tissue on the top and bone tissue on the bottom) ( Figure 5 c), which are specific markers of cartilage and bone formation, respectively. The results showed that the positive expression of Aggrecan (green) and BMP-2 (red) in the GMA-Col group was the highest compared with the other groups, and showed an increasing trend over time. Figure 5 e and Figure 5 The semi-quantitative analysis in f further confirmed Figure 5 The observation results in c showed that the expressions of Aggrecan and BMP-2 in the GMA-Col group increased over time and were the highest compared with the other groups at different time points (P < 0.01).
[0168] ⑤ According to the morphological scoring criteria of tendon-bone interface tissue (Table S4) and the aforementioned histological examination, the integrity of the regenerated tendon-bone interface tissue in different groups was scored. Compared with the other groups, the GMA-Col group showed the highest tendon-bone interface morphology, integrity, and maturity at 12 weeks ( Figure 5 g).
[0169] 4) GMA-Col repairs the histological structure of bone tissue at the injured site
[0170] ① First, the collected rotator cuff tendon-humerus complexes of each group were fixed in 4% (w / v) paraformaldehyde for 48 hours. After fixation, the samples were scanned and imaged by Micro-CT (Zeiss 520Versa). Imaging examinations were performed 4 weeks and 12 weeks after implantation. Three-dimensional reconstruction, screenshots and data measurements were performed from both sides of the supraspinatus tendon footprint area of the humeral head to the outside of the humeral head. The analysis parameters included bone density (BMD, g / cm3), bone volume / total integer (BV / TV, %), trabecular number (Tb.N, mm -1) and trabecular thickness (Tb.Th, mm) (n=3). For high-resolution Micro-CT scanning and imaging, each composite was initially cut into small pieces of 5 mm on each side using an electric saw. The slices were then fixed in 4% (w / v) paraformaldehyde for 48 hours and then rinsed in ultrapure water for 5 hours. Subsequently, the samples were immersed in Lugol's iodine solution for 48 hours to enhance soft tissue contrast, rinsed with 70% ethanol, and stored in anhydrous ethanol until Micro-CT scanning. The data collected from the Micro-CT scans were reconstructed using the XMR Reconstructor software provided with the scanner, followed by manual center offset correction.
[0171] ②High-resolution micro-CT was used to observe the microstructural details of the tendon-bone interface in each group 12 weeks after surgery. Figure 6 The low-magnification micro-CT image in a intuitively demonstrates the structural transition from the upper tendon tissue to the underlying bone tissue (the interface is marked by a red dashed line). The results showed that the contrast between the TBI and tendon tissue areas (i.e., above the red dashed line) in the AHF-Col and GMA-Col groups was significantly higher than that in the control and RF-Col groups, which may indicate that the newly formed TBI and tendon tissue had a higher density.
[0172] ③ Figure 6 The high-magnification micro-CT images in b further compared the microstructural details of the TBI tissues that were closely connected to the bone tissue in the AHF-Col and GMA-Col groups. The results showed that the newly formed TBI tissues in the GMA-Col group had a denser tissue structure compared with the AF-Col group. In addition, micro-CT was used to observe the healing of the damaged tendon-bone at 8 and 12 weeks after surgery ( Figure 6 c). Poor bone defect healing was observed in the control group, whereas the bone tissues in the other groups were more continuous (as indicated by the red dashed box) and the cortical bones were fuller (marked by the red arrow).
[0173] ④ Quantitative analysis showed that the bone volume / total volume (BV / TV), bone mineral density (BMD) and trabecular number (Tb.N) of the GMA-Col group were the highest among all groups ( Figure 6 df).
[0174] 5) GMA-Col repairs the kinematic function of tendon-bone tissue at the injured site
[0175] ① 12 weeks after surgery, gait analysis was performed on each group of experimental white rabbits using an animal gait detector. The animal gait detector includes a glass plate runway with a high-definition camera installed on one side of the runway to capture and record the gait of the test animals. The feeding box next to the device can induce the animals to quickly cross the glass runway, which is conducive to the experiment. Before the gait analysis test, the animals were trained for about 1 week to eliminate the interference of environmental, habitual and other factors on the animal's gait. Then the gait analysis system was used to automatically identify, analyze and calculate the body parameters and speed parameters of the rabbit's footprints, so as to objectively and accurately reflect the changes in the animal's gait. ( Figure 7 a)
[0176] ② Figure 7 b further illustrates the rotator cuff (marked with yellow dots) and other key areas associated with forelimb movement (i.e., ankles, elbows, toes, and neck, e.g. Figure 7 c) through continuous motion capture (each interval is one frame).
[0177] ③ The group implanted with GMA-Col showed the best recovery of motor ability. Figure 7 d) and the highest body height during exercise ( Figure 7 These results were further confirmed by quantitative analysis in e).
[0178] ④ In addition, the changes in the movement angle of the rotator cuff relative to the neck and elbow during exercise were quantitatively analyzed ( Figure 7 f and 7g) to assess the flexibility of the rabbit shoulder joint. The results showed that the tissue implanted with GMA-Col achieved the greatest range of angular changes of the rotator cuff relative to the neck and elbow during movement, confirming the best restoration of shoulder joint flexibility.
[0179] ⑤ Subsequently, biomechanical tests were performed to evaluate the healing quality of the rotator cuff ( Figure 7h). All biomechanical tests were performed using a material mechanics testing system (Instron-5566, USA). A total of 4 rabbit rotator cuff tendon-humerus complex specimens were tested in each group. The specimens used for biomechanical testing retained the upper limb bones and infraspinatus muscles for easy clamping, and other soft tissues were removed. Before starting the test, the specimens were placed in a room temperature environment for 1 hour to warm up. In order to reduce sliding, the humeral head and upper limb bones were fixed in a special mold with dental tray powder added to the mold. The infraspinatus tendon was sutured with medical gauze to increase friction, and then the specimen was fixed. After applying a preload of 1N at a test speed of 5mm / min (strain rate of 0.8% / s), the rotator cuff specimens were preconditioned for a total of 20 cycles. The ultimate tensile load (N), ultimate tensile stress (MPa) and stiffness (N / mm) were recorded and calculated. The stiffness (N / mm) of each specimen was calculated from the slope of the linear region of the load-deformation curve from the maximum load to the failure point.
[0180] ⑥The results showed that the ultimate failure load of the GMA-Col group ( Figure 7 i) Strength ( Figure 7 j) and stiffness ( Figure 7 k) was the highest among all groups.
[0181] Overall, implantation of GMA-Col promoted optimal restoration of motor function and mechanical properties from tendon to bone in the rabbit RCT model.
[0182] The above description of the embodiments is to facilitate the understanding and use of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a gradient mineralized collagen fiber membrane, characterized in that: The highly oriented collagen fiber membrane is placed vertically at the bottom of the container along the fiber orientation direction, and then the mineral solution is continuously injected into the container at a rate of 0.3-0.7 ml / h, and mineralized at a constant temperature of 35°C-42°C. After the mineralization is completed, the excess mineralized liquid on the surface is removed, and then it is dried at a constant temperature of 35°C-42°C; The pH value of the mineral solution is 7.37-7.49, and it includes a solution A component and a solution B component that are uniformly mixed in equal volumes; in, Solution A component is a solution having a mixing ratio of 0.1M CaCl2·2H2O and 0.02-0.04g / ml polyaspartic acid solid powder; Solution B component is at least one of a mixed solution of 0.1M Na2HPO4 and 0.04-0.08g / ml polyacrylic acid solid powder or a mixed solution of 0.1M K2HPO4 and 0.04-0.08g / ml polyacrylic acid solid powder.
2. The method for preparing the gradient mineralized collagen fiber membrane according to claim 1, characterized in that: The mineral solution is continuously injected into the container at a rate of 0.5-0.6 ml / h; The temperature for mineralization and / or drying is 37°C-39°C; The pH value of the mineral solution is 7.40-7.42; The content of polyaspartic acid solid powder in component A of solution is 0.03-0.04 g / ml; The content of polyacrylic acid solid powder in component B of solution is 0.04-0.06 g / ml; The content of the polyaspartic acid solid powder in the solution A component: the content of the polyacrylic acid solid powder in the solution B component is 1: (1.5-2.5).
3. The method for preparing the gradient mineralized collagen fiber membrane according to claim 1, characterized in that: The molecular weight of the polyaspartic acid solid powder is 10-11 kDa; the molecular weight of the polyacrylic acid solid powder is not less than 2000 Da; The mass concentration ratio of the polyaspartic acid solid powder to the polyacrylic acid solid powder is 1:2; The gradient mineralized layer of the prepared gradient mineralized collagen fiber membrane has the same width and thickness as the unmineralized layer; The length ratio of the gradient mineralized layer to the unmineralized layer of the prepared gradient mineralized collagen fiber membrane is (7-8): (2-3).
4. The method for preparing the gradient mineralized collagen fiber membrane according to claim 1, characterized in that: The mineral solution is selected from any of the following formulations: Ⅰ: 9mM CaCl2·2H2O+4.2mM K2HPO4+50μg / mL pAsp; Ⅱ: 10.0mM CaCl2·2H2O+6.0mM Na2HPO4+90mM NaCl+350μg / ml PAA+10mM L-Glutamicacid; III: 1.67mM CaCl2·2H2O+9.5mM Na2HPO4+150mM NaCl+240μg / mL pAsp+Sodiumcitrate; IV: SBF + 180 μg / mL pAA + 2.5 wt% TPP; or Ⅴ: Solution A: 0.1M CaCl2·2H2O+0.03g / ml pAsp; Solution B:0.1M Na2HPO4+0.06g / ml PAA.
5. The method for preparing the gradient mineralized collagen fiber membrane according to claim 1, characterized in that: The collagen fiber membrane is a highly oriented collagen fiber membrane, and the preparation method of the highly oriented collagen fiber membrane comprises: (1) Soaking the collagen gel membrane stretched to 100%-200% strain in a PBS solution for 1-4 hours, while continuously loading both ends of the membrane to maintain the oriented structure; (2) After soaking, the collagen gel membrane is placed in an NH3 atmosphere for 12 to 36 hours, and external force is continuously applied to both ends of the collagen gel membrane.
6. The method for preparing the gradient mineralized collagen fiber membrane according to claim 5, characterized in that: Soak the collagen gel membrane stretched to 200% strain in 0.1M PBS solution for 2-3 hours; or, After soaking, the collagen gel membrane was placed in an NH3 atmosphere for 24-30 hours.
7. A gradient mineralized collagen fiber membrane, characterized in that: Includes gradient mineralized and unmineralized layers; The gradient mineralization layer includes type I collagen and a spatially gradient distributed HAp component. The unmineralized layer is composed of type I collagen.
8. The gradient mineralized collagen fiber membrane according to claim 7, characterized in that: The type I collagen component has a highly oriented fiber structure, and the Herman orientation factor of the fiber structure is distributed in the range of 0.92-0.99; The width between the gradient mineralized layer and the unmineralized layer is 1-1.5 times the width of the unmineralized layer, and the thickness of the gradient mineralized layer is 1-1.5 times the thickness of the unmineralized layer; The length ratio of the gradient mineralized layer to the unmineralized layer is (1-9):(1-9).
9. The use of the gradient mineralized collagen fiber membrane according to claim 7 or 8, characterized in that: The application of the gradient mineralized collagen fiber membrane in tendon-bone repair.
10. The use according to claim 9, characterized in that: The application includes one or more of the following: (1) It has an aligned hierarchical fibrous structure and enhances mechanical properties in the alignment direction: (2) Supporting the adhesion and continued proliferation of cells associated with tendon and bone healing; (3) allowing the provision of different local physicochemical environments to selectively promote cell differentiation into tendon, cartilage, or bone, thereby reconstructing the gradient cell phenotype of tendon-bone interface tissue; (4) Enhance the mechanical properties of the healing injury site and the recovery of the animal's motor function.
Citation Information
Cited By
Irradiation crosslinking collagenous fiber material and preparation method and application thereof
CN119613775A
Bionic collagen membrane material capable of regulating and controlling electric field period as well as preparation method and application of bionic collagen membrane material
CN120818865A
